Effective Strategies for Teaching Chinese Picture Book Reading in Primary Schools - Zhang, Dan; Wu, Wanqingyang; Ding, Long (Journal of Education and Educational Technologies, 2023)
Picture books are books with pictures as the main content. As the name suggests, they are "drawn books", which contain rich situational stories. To allow children to read picture books, understand them, and understand their true intentions while fully relaxed, the teacher should cultivate children's logical thinking, imagination, language skills, predictive reasoning skills, etc. through meaningful questioning and guidance. Therefore, it is urgent to effectively carry out picture book reading education! The interweaving of global trade wars and global value chains is having a profound impact on the global economy and multinational enterprises. Trade war is an important manifestation of economic and trade frictions between countries, involving the imposition and countermeasures of tariffs, trade restrictions and other trade barriers. These measures not only affect the scale and pattern of international trade, but also lead to the reconstruction and adjustment of global value chain, which poses new challenges to the operation strategy and development strategy of multinational enterprises.